A Content Analysis of Chemical Representations in Voltaic Cells Concept on General Chemistry Textbooks - Sakina, Nifela; Wiji, Wiji; Widhiyanti, Tuszie (FKIP - Universitas Riau, 2025)
Representations in chemistry are essential for supporting students' understanding of abstract concepts such as redox reactions and voltaic cells. However, many students experience difficulties due to the lack of integration among macroscopic, submicroscopic, and symbolic levels of representation in textbooks. This study aimed to evaluate the quality and integration of visual representations related to voltaic cells in general chemistry textbooks widely used in Indonesian undergraduate programs. A descriptive qualitative content analysis approach was employed using an evaluation rubric developed by Gkitzia, which includes five criteria: type of representation, interpretation of surface features, relatedness to text, existence and clarity of captions, and the degree of correlation between components in multiple representations. Data were collected from five textbooks selected through purposive sampling and analyzed both qualitatively and quantitatively. The results showed that while most textbooks present macroscopic and symbolic representations adequately, submicroscopic levels are often lacking or fragmented. Common issues identified include insufficient labeling, missing or problematic captions, and weak text-image integration. Only a few textbooks provide well-developed hybrid representations. The study concludes that visual representations in textbooks still need significant improvement to support conceptual understanding. These findings provide insights for chemistry educators and textbook developers to design more pedagogically effective materials.